2010
DOI: 10.1007/s10620-010-1461-5
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hydrogen Sulfide Is an Anti-inflammatory Molecule in Dextran Sodium Sulfate-Induced Colitis in Mice

Abstract: Taken together, the results indicated that the inhibition of endogenous H(2)S generation caused the deterioration of DSS-induced colitis. We conclude that physiological H(2)S might act as an anti-inflammatory molecule in colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 36 publications
0
69
0
2
Order By: Relevance
“…In dextran sulfate-induced ulcerative colitis in rats, administration of a sulfide binding compound, bismuth subsalicylate, reduced fecal sulfide release but did not protect against colitis, indicating that elevated sulfide does not play a role in the etiology of colitis, at least in this model [214]. On the other hand, other studies have reported a protective role for H 2 S in healing of gastric ulcers and colitis [215,216], gastric injury caused by anti-inflammatory nonsteroidal drugs [164] and resolution of colitis [168]. It is important to note that experimental models of ulcerative colitis might be substantially different from the naturally occurring disease and the effect of H 2 S could be dependent on both the experimental model as well as the stage of colitis.…”
Section: Cellular and Physiological Processes Regulated By H2smentioning
confidence: 95%
“…In dextran sulfate-induced ulcerative colitis in rats, administration of a sulfide binding compound, bismuth subsalicylate, reduced fecal sulfide release but did not protect against colitis, indicating that elevated sulfide does not play a role in the etiology of colitis, at least in this model [214]. On the other hand, other studies have reported a protective role for H 2 S in healing of gastric ulcers and colitis [215,216], gastric injury caused by anti-inflammatory nonsteroidal drugs [164] and resolution of colitis [168]. It is important to note that experimental models of ulcerative colitis might be substantially different from the naturally occurring disease and the effect of H 2 S could be dependent on both the experimental model as well as the stage of colitis.…”
Section: Cellular and Physiological Processes Regulated By H2smentioning
confidence: 95%
“…Indeed, there remains conflicting evidence regarding the precise role of H 2 S in the gut[344,347]. On one hand, it appears that lower concentrations of endogenously derived H 2 S exert beneficial cytoprotective, antioxidant and anti-inflammatory actions[344,348351], while on the other, increased H 2 S formation by SRB can promote oxidant formation, impair colonic epithelial H 2 S detoxification and induce cytotoxicity and disruption of intestinal barrier integrity, thereby driving local and systemic inflammation[344,347,352,353]. Certainly, further understanding of the roles that H 2 S concentration, substrate, and location play in inflammation and nitrate metabolism remain to be more fully elucidated.…”
Section: Dysbiosis Of the Microbiome In Pulmonary Hypertension And Vascmentioning
confidence: 99%
“…2). The widely used CSE inhibitor, dl -proparylglycine, for example, can increase disease severity in animal models of colitis [96], myocardial ischemia–reperfusion-induced injury [97], and also has anti-hyperalgesic effects [98] and has reported inflammatory as well as anti-inflammatory effects in rodent models [21]. These studies indicate that the inhibition of H 2 S biosynthetic enzymes, and therefore, the production of H 2 S within tissues and cells typically leads to increased disease severity which effects are reversed by the use of H 2 S donor molecules.…”
Section: Pharmacological Approaches To Manipulate H2s Levels Within Bmentioning
confidence: 99%